2010
DOI: 10.1111/j.1365-2966.2010.16740.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactic stellar haloes in the CDM model

Abstract: We present six simulations of galactic stellar haloes formed by the tidal disruption of accreted dwarf galaxies in a fully cosmological setting. Our model is based on the Aquarius project, a suite of high resolution N-body simulations of individual dark matter haloes. We tag subsets of particles in these simulations with stellar populations predicted by the Galform semi-analytic model. Our method self-consistently tracks the dynamical evolution and disruption of satellites from high redshift. The luminosity fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

70
765
3
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 540 publications
(842 citation statements)
references
References 168 publications
70
765
3
4
Order By: Relevance
“…These smaller halos are severely affected by the larger potential well of the host and are tidally stripped or fully disrupted, appearing on the sky as substructures in the form of streams and satellites (e.g., Bullock & Johnston 2005;Springel et al 2006;Cooper et al 2010). Observationally, the detection of substructures in the halos of massive galaxies agrees with this scenario (e.g., Martínez-Delgado et al 2010;Atkinson et al 2013;Martin et al 2014).…”
Section: Introductionsupporting
confidence: 72%
“…These smaller halos are severely affected by the larger potential well of the host and are tidally stripped or fully disrupted, appearing on the sky as substructures in the form of streams and satellites (e.g., Bullock & Johnston 2005;Springel et al 2006;Cooper et al 2010). Observationally, the detection of substructures in the halos of massive galaxies agrees with this scenario (e.g., Martínez-Delgado et al 2010;Atkinson et al 2013;Martin et al 2014).…”
Section: Introductionsupporting
confidence: 72%
“…The parameters of the DF include the mass, M, and concentration, c, of the NFW halo, the tracer velocity anisotropy, β, and the double-power-law slopes and pivot radius of the tracer density profile, α, γ and r p . Their values are chosen to best match the distribution of mock stars inside an MW-sized halo in the Aquarius simulation (Cooper et al 2010), with M = 1.83 × 10 12 M , c = 16.2, β = 0.715, r p = 69.0 kpc, α = 2.30, γ = 7.47. The mock tracers generated according to this f (E, L) are expected to be a self-consistent, yet simplified, realization of the distribution of stars in the MW.…”
Section: Data : I D E a L T R Ac E R Smentioning
confidence: 99%
“…In particular, Wang et al (2015) applied the f (E, L) method to mock stellar haloes (Cooper et al 2010) constructed from the Aquarius simulations of cold dark matter ( CDM) galactic haloes (Springel et al 2008) and found significant biases in the fitted masses. These biases suggest that the proposed f (E, L) DF does not describe well the observed phasespace distribution of the mock stars.…”
Section: Introductionmentioning
confidence: 99%
“…In present-day ETGs, these stars contribute to lowering the metallicity in the regions where they have been accreted, i.e., at large galactocentric radii. These outermost regions are expected to show generally shallow metallicity gradients because of the dynamical mixing of pre-existing and accreted stars (Kobayashi 2004;Di Matteo et al 2009;Cooper et al 2010;Font et al 2011).…”
Section: Introductionmentioning
confidence: 99%